Optimal levels of oxygen deficiency in the visible light photocatalyst TiO2−x and long-term stability of catalytic performance. (November 2016) - Nakano, Takuma; Ito, Ryosuke; Kogoshi, Sumio; Katayama, Noboru
Abstract: The dependence of the visible light-responsive photocatalytic activity of oxygen deficient TiO2 (TiO2− x ) prepared by Ar/H2 plasma surface treatment on the degree of oxygen deficiency ( x ) was assessed to determine the deficiency region associated with highest performance. The highest activity was obtained at x =0.06 (TiO1.94 ). The maximum visible light activity for this material, estimated from the formaldehyde (HCHO) removal rate, was three times higher than that exhibited by nitrogen-doped TiO2 (TiO2− x N x ). The catalytic ability was found to decrease over the first week after fabrication of the material, after which it became stable, and the performance of TiO2− x at this point was found to be nearly equal to that of TiO2− x N x . The results of ab initio calculations of density of states for TiO2− x suggest that new oxygen deficiency states emerge at almost the exact center between the valence and conduction bands when x >0.06, which increases the recombination rate between electrons and holes. Therefore the declining performance of TiO2− x at larger x values is attributed to the emergence of new oxygen deficient states. Highlights: The optimal extent of oxygen deficiency in the visible light photocatalyst TiO2− x is obtained. The density of states of TiO2− x are calculated. The long-term deterioration of the performance of TiO2− x is obtained.